The Psychology of Trauma in Toni Morrison's Beloved (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Toni Morrison's novel Beloved (1987) stands as one of the most psychologically penetrating literary responses to the institution of slavery in American fiction. This paper investigates the psychology of trauma as it is constructed and mediated through Morrison's narrative, attending specifically to the ways in which the novel dramatises the enduring psychological consequences of enslavement on its principal characters. Drawing on established frameworks from trauma theory-including Judith Herman's (1992) model of complex post-traumatic stress, Bessel van der Kolk's (2014) neurobiological account of traumatic memory, and Cathy Caruth's (1996) theorisation of trauma's unclaimed temporality-the study examines how Morrison renders the interior lives of Sethe, Baby Suggs, and Paul D as sites of psychological rupture, dissociation, and incomplete recovery. The analysis demonstrates that the novel operates simultaneously as literary testimony and as a sophisticated engagement with the clinical and theoretical literature on trauma, anticipating numerous insights that contemporary psychology has since formalised. The paper further argues that Morrison's representation of intergenerational trauma, embodied memory, and community-based healing offers a model of recovery that extends beyond the individual toward the collective-a dimension of traumatic experience that conventional clinical frameworks have historically underweighted. The findings carry implications for both literary studies and the psychology of historical and collective trauma.